Kantische Antworten auf Kants kasuistische Fragen, die vollkommenen Pflichten gegen sich selbst betreffend - Eleonora Oggionni, Eva Marta (Con-Textos Kantianos. International Journal of Philosophy, 2017)
The paper engages with the Casuistic questions posed in the book on the Perfect Duties to Oneself, in the Metaphysical Principles of the Doctrine of Virtue of the Metaphysic of Morals. It investigates whether it is possible to identify Kant’s literal answers to the casuistic questions that Kant himself poses, concluding that it is not. Therefore, Kantian answers rather than Kant’s answers are discussed. The paper’s outcome supports a rigorist interpretation of Kant’s ethics.
Keywords: Kant; Doctrine of Virtue; Casuistic Questions; Duties to the Self